Can Drones Reduce Plant Protection Costs in Agriculture? – An Experience Based Analysis - Ramanjaneyulu, A. V.; Sainath, N.; Swetha, D.; Ramprasad, B.; Varma, N. R. G.; Reddy, R. Uma; Jagadeeshwar, R.; Nagarjuna, T. (Chronicle of Bioresource Management, 2021)
The usage of drones for carrying out various need based operations in Agriculture has been increasing across several nations in the world including India. Changes in farm sector are needed to curtail the problem of green house gas emissions and mitigate ill effects of global climate change, thus, safeguard the environment. Drones are found to manage the resources on agricultural farms very efficiently. This uncrewed air vehicle technology can help reduce plant protection cost, save labour and time and improve farm efficiency. However, India is at infancy stage and yet to reap full benefits. Capacity building is required for drone operators in agriculture in order to upscale and outscale the technology. There is a need for promoting young entrepreneurs in drone technology through subsidies in order to provide employment as well as take the technology forward at a faster rate.